Ethical leadership and TMT decision-making of corporate social responsibility – a perspective of self-determination theory - Meng, Jia-jia; Wang, Xue-dong; Xie, Ming-yi; Hao, Zhi-ling; Yang, Jia-lu; Liu, Yu-bing (Frontiers in Psychology, 2023)
This study examines the impact of ethical leadership on top management team (TMT) decisionmaking regarding corporate social responsibility (CSR), considering the mediating role of TMT passion and the moderating role of performance stress. The study distinguishes between TMT harmonious and obsessive work passion and categorizes CSR as proactive and reactive. The findings reveal the following: (1)Ethical leadership positively influences proactive CSR, with TMT harmonious work passion acting as a positive mediator and TMT obsessive work passion playing a negative mediating role; (2) Ethical leadership positively affects reactive CSR, with both TMT harmonious and obsessive work passion serving as positive mediators; (3) Performance stress diminishes the impact of ethical leadership on TMT harmonious work passion; however, it amplifies the effect on TMT obsessive work passion. Consequently, the mediating effect of TMT harmonious work passion weakens, while the mediating effect of TMT obsessive work passion strengthens. This study emphasizes the significant role of TMT in CSR strategic decision-making and proposes a novel mediating mechanism through which ethical leadership drives CSR decision-making by considering TMT work passion. These findings reconcile the theoretical-practical conflict and have important theoretical and practical implications for enterprises in fulfilling their social responsibility.